Buffalo Bill's dead now [large type] - Coel, Margaret, 1937- (Coel, Margaret, 1937- Wind River mystery, 2012)
After over 120 years, the regalia worn by Arapaho Chief Black Heart in Buffalo Bill's Wild West Show were to be returned to his people. But the cartons that arrived at the Arapaho museum were empty. Rancher and Indian artifact collector Trevor Pratt, who had them shipped from Germany, believes thieves stole them en route. But Vicky Holden and Father John O'Malley suspect Trevor knows more about the theft than he's telling.